THU0207 Acute serum amyloid a and TLR2 activation induces pro-inflammatory mechanisms in a novel EX vivo temporal artery explant culture/model of giant cell arteritis. (23rd January 2014) - Molloy, D.; Connolly, M.; McCormick, J.; Haroon, M.; Veale, D.J.; Murphy, C.; Molloy, E.; Fearon, U.
Abstract : Background: Giant cell arteritis (GCA) is a common form of primary vasculitis characterised by dysfunctional vessels and inflammatory infiltration, however the underlying mechanisms involved in regulating these processes have yet to be elucidated. This study examines the role of acute serum amyloid A (A-SAA) and TLR2 activation in mediating pro-inflammatory pathways and angiogenesis using temporal artery (TA) whole tissue explants ex-vivo. Methods: Ex vivo TA explant cultures were established from GCA patients direct from surgery and the effect of pro-inflammatory stimuli A-SAA (10μg/ml) and a TLR2 agonist Pam3CYSK4 (1μg/ml) on Ang2, MMP2, MMP9, IL-6 and IL-8 was quantified by ELISA and gelatin zymography. Furthermore, myofibroblast outgrowth from TA explants was assessed using matrigel assays over a time course of 1-15 days. Results: Ex vivo TA explant cultures spontaneously released pro-inflammatory mediators, maintained cell viability and histological morphology, thus closely reflecting the in vivo microenvironment. A-SAA and Pam3CSK4 induced expression of instability growth factor Ang2 (p<0.05) and MMP2 and MMP 9 which are involved in blood vessel invasion. A-SAA and Pam3CSK4 significantly induced IL-8 expression (p<0.05), with no significant effect observed for IL-6. A-SAA and Pam3CSK4 induced myofibroblast outgrowths from TA explants embedded in matrigel over a time course of 1-15 days. In parallel, Ang2, MMP2/9 and pro-inflammatory chemokine IL-8 were induced in myofibroblast outgrowth cultures in response to A-SAA, and to a lesser extent Pam3CSK4. Conclusions: Using a novel ex vivo TA explant culture we demonstrate for the first time that A-SAA and TLR2 activation induce angiogenic factors, chemokine expression and promote migrational/invasive processes as shown by their effect on myofibroblast outgrowths. Since TLR2 can mediate the effect of A-SAA, these results suggest that this pathway may represent a potential therapeutic target for GCA. Disclosure of Interest: D. Molloy: None Declared, M. Connolly: None Declared, J. McCormick: None Declared, M. Haroon: None Declared, D. Veale Grant/Research support from: Wyeth, GSK, Abbott, Opsona, Consultant for: Wyeth, GSK, Abbott, Pfizer, Schering Plough, Centocor, Speakers Bureau: Wyeth, GSK, Abbott, Pfizer, Schering Plough, Centocor, Mundipharma, C. Murphy: None Declared, E. Molloy: None Declared, U. Fearon: None Declared